Leveraged Exchange-Traded Funds A Comprehensive Guide to Structure, Pricing, and Performance - Charupat, Narat; Miu, Peter; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
Leveraged Exchange-Traded Funds (LETFs) are publicly-traded funds that promise to provide daily returns that are in a multiple (positive or negative) of the returns on an index. To meet that promise, the funds use leverage, which is typically obtained through derivatives such as futures contracts, forward contracts, and total-return swaps. As of the end of 2012, there were over 250 LETFs in North America with total assets of approximately $32.24 billion. While the amount of assets held by these funds is still small, their popularity continues to grow as their trading volume is significantly larger and much more dynamic than traditional, non-leveraged ETFs. This comprehensive guide to LETFs provides high-level practitioners and researchers with a detailed reference tool for navigating the market and making informed investment decisions. Written from a measured analytical perspective, Miu and Charupat use clear and concise explanations of all important aspects of LETFs, focusing on such key elements as structure, pricing, performance, regulations, taxation, and trading strategies. The first two chapters set the stage for the book by identifying exactly what LETFs are and how they are regulated. The following chapters then look to bridge theory with practice to dive deep into the mechanics, portfolio rebalancing techniques, and daily compounding effects that make investing in these funds so lucrative.
Keywords: Capital market; Investment banking; Securities; Banks and banking